The Enduring Legacy of Educational Institutions: Evidence from Hyanggyo in Pre-Modern Korea - Yeonha Jung; Minki Kim; Munseob Lee (Institute of Labor Economics (IZA), 2025)
This study examines the long-term impact of Hyanggyo, state-sponsored educational institutions established during the early Joseon Dynasty in Korea (1392-1592), on human capital accumulation. Although these schools largely ceased functioning as educational centers by the late 16th century, their influence has endured to the present day. Drawing on a newly constructed township-level dataset, we find a robust positive association between historical exposure to Hyanggyo and modern educational attainment. This relationship appears to be driven by enduring local demand for education, supported by three complementary findings. First, regions with greater historical exposure experienced larger gains in Japanese literacy during colonial era school expansions. Second, residents in these areas express stronger pro-education attitudes today. Third, historically exposed regions exhibited lower fertility rates, consistent with a quantity–quality tradeoff in parental investment. Together, our findings highlight the lasting legacy of early educational institutions.
Keywords: I23; J24; N35; O15; 330; historical institutions; human capital; Hyanggyo; Joseon; cultural transmission